2016
DOI: 10.3390/md14020027
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Sources of Prebiotics: Seaweeds and Microalgae

Abstract: In recent years, scientists have become aware that human microbiota, in general, and gut microbiota, in particular, play a major role in human health and diseases, such as obesity and diabetes, among others. A large number of evidence has come to light regarding the beneficial effects, either for the host or the gut microbiota, of some foods and food ingredients or biochemical compounds. Among these, the most promising seem to be polysaccharides (PS) or their derivatives, and they include the dietary fibers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(154 citation statements)
references
References 167 publications
(228 reference statements)
4
149
0
1
Order By: Relevance
“…Indeed, several compounds, including γ-linolenic acid, active fatty acid lauric and palmitoleic acid, have been attributed to the antimicrobial activities of S. platensis (El-Sheekh et al, 2014). With its prebiotic properties (Beheshtipour et al, 2013;de Jesus Raposo et al, 2016), S. platensis is known to possess a stimulating effect on the growth of LAB (Lactobacillus acidophilus, Lactobacillus casei and Streptococcus thermophilus) (Bhowmik et al, 2009). In broiler chickens, S. platensis administration has been associated with the increased intestinal population of LAB (Shanmugapriya et al, 2015b), while in Japanese quails, feeding such algae tended to increase the count of intestinal lactobacilli (Yusuf et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several compounds, including γ-linolenic acid, active fatty acid lauric and palmitoleic acid, have been attributed to the antimicrobial activities of S. platensis (El-Sheekh et al, 2014). With its prebiotic properties (Beheshtipour et al, 2013;de Jesus Raposo et al, 2016), S. platensis is known to possess a stimulating effect on the growth of LAB (Lactobacillus acidophilus, Lactobacillus casei and Streptococcus thermophilus) (Bhowmik et al, 2009). In broiler chickens, S. platensis administration has been associated with the increased intestinal population of LAB (Shanmugapriya et al, 2015b), while in Japanese quails, feeding such algae tended to increase the count of intestinal lactobacilli (Yusuf et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to S. platensis in particular, this microalga has high contents of protein, essential amino acids, vitamins, minerals, essential fatty acids and pigments (Beheshtipour et al, 2013;Holman & Malau-Aduli, 2013). Spirulina platensis is also rich in polysaccharides, which may function as prebiotics (Beheshtipour et al, 2013;de Jesus Raposo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides from algae, for example β-glucans from C. vulgaris, and spirulina biomass are already recognised and accepted as dietary prebiotics (Jiménez-Escrig et al 2013;de Jesus Raposo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary seaweeds have been found to have significant prebiotic effects that influence Bifidobacterium populations (de Jesus et al 2016). Wang reported that 2.5 % alginate supplementation in rats increased Bifidobacterium by 13-fold compared to the control group (Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%